Laboratory assessment of a head impact sensor for youth soccer ball heading impacts using an anthropomorphic test device - Patton, D. A.; Huber, C. M.; Douglas, E. C.; Seacrist, T.; Arbogast, K. B. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
Recent advances in technology have enabled the development of instrumented equipment, which estimate the head impact kinematics of athletes in vivo. One such headband-mounted impact sensor is the SIM-G (Triax Technologies, Norwalk, CT, USA), which has been previously used to investigate the biomechanics of soccer heading by human subjects. Previous studies have evaluated the accuracy of the SIM-G for pure rotation and pendulum, impulse hammer and drop rig impacts. The current study used a soccer ball heading model to evaluate the accuracy of the SIM-G. A soccer ball was projected at the head of an anthropomorphic test device (ATD) representing a 10-year-old to replicate the heading maneuver at various impact sites, angles and speeds previously identified in youth soccer. Linear regression revealed that the SIM-G sensor overestimated the peak angular velocity and linear acceleration recorded by the ATD headform by approximately 44% and 105%, respectively. Tests in which the ball directly contacted the SIM-G sensor resulted in the largest peak linear accelerations. Glancing impacts were significantly associated with a decrease in percentage error of the SIM-G sensor peak angular velocity data relative to the ATD reference data. While it may not demonstrate accuracy in estimating the magnitudes of head impacts, the SIM-G remains a useful tool to provide estimates of head impact exposure for soccer players.